Nyah Lasem Museum: A Space for Lifelong Learning and the Recontextualization of Lasem’s 20th Century Cultural and Historical Identity - Ilham Baskoro; Maulidiyah Rahmawati; Yoanka Noveira Loveana; Muryadi; Ikhsan Rosyid Mujahidul A. (Biokultur, 2026)
This study examines the Nyah Lasem Museum as a space for lifelong learning that represents the process of recontextualizing the cultural identity of coastal Javanese communities in the twentieth century. The museum is located in the Old Town area of Lasem, a historical center of multiethnic interaction between Chinese and Javanese communities, as well as one of the main batik production hubs that flourished during the colonial period. Employing a historical methodology combined with qualitative research through field documentation and a documentary video output, this study explores how the Nyah Lasem Museum functions not only as a repository of artifacts but also as a living space that constructs cultural dialogues between the past and the present. The findings reveal that the Nyah Lasem Museum plays a crucial role in preserving the community’s collective memory by highlighting alternative narratives, particularly those of Chinese women or “nyonyah” who have long been marginalized in mainstream historiography. The museum demonstrates a participatory and inclusive model of community-based preservation rooted in local cultural values. The management initiative led by the Lasem Heritage Foundation shows a concrete effort to engage the local community in sustaining cultural heritage while strengthening Lasem’s cultural identity as a historically rich coastal town. In a broader context, this study asserts that the Nyah Lasem Museum serves not only as a conservation space for historical artifacts but also as a symbol of continuous cultural learning. The museum presents a potential model of heritage management that harmoniously integrates educational, social, and recreational functions. Consequently, the Nyah Lasem Museum can be positioned as a tangible representation of the museum of lifelong learning concept in Indonesia, placing the community as an active subject in the preservation and development of local culture.